Seminal vesicle secretory protein 7, PATE4, is not required for sperm function but for copulatory plug formation to ensure fecundity†. Issue 4 (18th November 2018) - Noda, Taichi; Fujihara, Yoshitaka; Matsumura, Takafumi; Oura, Seiya; Kobayashi, Sumire; Ikawa, Masahito
Abstract: Seminal vesicle secretions (SVSs), together with spermatozoa, are ejaculated into the female reproductive tract. SVS7, also known as PATE4, is one of the major SVS proteins found in the seminal vesicle, copulatory plug, and uterine fluid after copulation. Here, we generated Pate4 knockout (−/−) mice and examined the detailed function of PATE4 on male fecundity. The morphology and weight of Pate4 −/− seminal vesicles were comparable to the control. Although Pate4 −/− cauda epididymal spermatozoa have no overt defects during in vitro fertilization, Pate4 −/− males were subfertile. We found that the copulatory plugs were smaller in the vagina of females mated with Pate4 −/− males, leading to semen leakage and a decreased sperm count in the uterus. When the females mated with Pate4 −/− males were immediately re-caged with Pate4 +/+ males, the females had subsequent productive matings. When the cauda epididymal spermatozoa were injected into the uterus and plugged artificially [artificial insemination (AI)], Pate4 −/− spermatozoa could efficiently fertilize eggs as compared to wild-type spermatozoa. We finally examined the effect of SVSs on AI, and observed no difference in fertilization rates between Pate4 +/+ and Pate4 −/− SVSs. In conclusion, PATE4 is a novel factor in forming the copulatory plug that inhibits sequential matings and maintains spermatozoa in the uterus to ensure male fecundity. Abstract : The copulatory plug has dual functions not only to prevent subsequent matings but also to maintain proper sperm count for fertilization in the female reproductive tract, as a winner-take-all strategy to advance male reproduction.